THE RECONSTRUCTION OF VALUES IN HANDLING TERRORISM BASED ON PANCASILA - Bahtiyar Efendi; Anis Mashdurohatun; Sri Endah Wahyuningsih (International Journal of Law Reconstruction, 2022)
The purpose of the research is to find out and examine the reconstruction of terrorism prevention policies in the digitalization era that is oriented towards Pancasila justice. The approach method used a normative juridical approach. The results of the research that show that the legal reconstruction is carried out by adding special counter-terrorism efforts, namely in the form of observation, supervision and control of all forms of activities related to terrorism, both from outside and from within the country. Then added efforts in the form of early supervision of the terrorism movement through digital technology as well as conducting international cooperation related to the prevention and eradication of terrorism, for this reason it is necessary to reconstruct the Prevention of Terrorism Crimes and the Protection of Investigators, Public Prosecutors, Judges, and Correctional Officers, then reconstruction of Protection For Investigators, Public Prosecutors, Judges, and Correctional Officers, the contribution of the research is expected to reconstruct policies for handling terrorism crimes based on the value of justice so that they are expected to be able to provide a renewal of thought in the theory of preventing and handling terrorism crimes through the thought of preventing terrorism crimes.